Processo de substituição de r22 em sistemas de refrigeração comerciais - Antunes, Arthur Heleno Pontes (2015)
This work reports an experimental investigation related to the drop-in process of HCFC22 in a commercial refrigeration system with a maximum capacity of 15 kW. Among the alternative refrigerants there are hydrocarbons (HCs) and synthetic refrigerants, HFC. The experimental facility is basically composed of analternative variable speed compressor (VSC), tube in tube heat exchangers and an electronic expansion valve (EEV). Different methodologies were addressed to this document. Initially, the systemoperated at the nominal frequency and has been configured to the same openning condition in the expansion valve. The limits of the refrigeration system were operated by factorial experimental designs. Therefore,there were presented response surfaces and metamodels, showing consistent tools to predict the cooling system behavior. Also, an analysis of the individual performance of each refrigerant was held in three different evaporation temperatures: -15ºC, -10ºC and -5ºC. All fluids, except R134a can be suitable to replace R22 in these specific applications. Both HCs and HFC32 provide the refrigeration capacity and COP greater than the original system. In addition, the environmental impact of each fluid was estimated by the TEWI method. HCs showed the lowest impacts, while HFC404A promoted the greatest damage to the environment. Finally, the analysis of the operating system with a Scroll compressor was made. Among the seven options to R22, only five refrigerants operated in stable condition. Moreover, even with handling system parameters, this class of compressors was less flexible to the proposed drop-in. In general, as a great technical contribution for refrigeration systems, this study found that, regardless of the installation capacity, the EEV/VSC pair functionality is an essential tool not only for the adaptation of an alternative fluid to the original compression cycle, as well as to reduce environmental impacts.